Muscarinic receptor binding of fesoterodine, 5-hydroxymethyl tolterodine, and tolterodine in rat tissues after the oral, intravenous, or intravesical administration - Shizuo Yamada; Shiori Kuraoka; Yoshihiko Ito; Yoshihisa Kato; Satomi Onoue (Elsevier, 2019)
The present study aimed to characterize muscarinic receptor binding of fesoterodine, 5-hydroxymethyl tolterodine (5-HMT), and tolterodine in bladder and other tissues of rats after their oral, intravenous, or intravesical administration. Muscarinic receptors in tissues were measured by using [N-methyl-3H]scopolamine methyl chloride ([3H]NMS). The in vitro binding affinity for muscarinic receptors was the highest by 5-HMT, followed by tolterodine and fesoterodine. Fesoterodine exhibited lower affinity in rat submaxillary gland than in detrusor muscle and urothelium. Muscarinic binding affinities of 5-HMT and tolterodine were similar among tissues. The duration of binding of oral fesoterodine to muscarinic receptors was longer in bladder than in submaxillary gland, heart, and lung, and its binding was little observed in colon and cerebral cortex. Binding activity of intravenous 5-HMT to muscarinic receptors was significantly observed in all tissues, except cerebral cortex, with a longer duration in bladder. Significant binding of bladder detrusor and urothelial muscarinic receptors was observed following intravesical instillation of 5-HMT. This selectivity may be attributed to the direct blockade of bladder receptors by excreted urinary 5-HMT. Thus, fesoterodine may be efficacious as a treatment for patients with overactive bladder. Keywords: Fesoterodine, 5-Hydroxymethyl tolterodine, Bladder, Muscarinic receptor binding, Bladder selectivity